2019
DOI: 10.1128/jb.00417-19
|View full text |Cite
|
Sign up to set email alerts
|

The msaABCR Operon Regulates the Response to Oxidative Stress in Staphylococcus aureus

Abstract: Staphylococcus aureus has evolved a complex regulatory network that controls a multitude of defense mechanisms against the deleterious effects of oxidative stress stimuli, subsequently leading to the pathogen’s survival and persistence in the hosts. Previously, we characterized the msaABCR operon as a regulator of virulence, antibiotic resistance, and the formation of persister cells in S. aureus. Deletion of the msaABCR operon resulted in the downregulation of several genes involved in resistance against oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 85 publications
(154 reference statements)
1
33
0
1
Order By: Relevance
“…Susceptibility to H 2 O 2 was reversed by iron sequestration or perR repressor gene deletion ( 238 ). Another study showed that the msaABCR operon of S. aureus regulates expression of genes involved in oxidative stress ( 239 ). Staphyloxanthin, a carotenoid pigment, is a strong antioxidant which is regulated by cold shock protein (CspA), alongside the organic hydroperoxide resistance gene which defends specifically against oxidative stress caused by organic hydroperoxides.…”
Section: Mechanisms Used By Macrophages To Kill S Aureus mentioning
confidence: 99%
See 1 more Smart Citation
“…Susceptibility to H 2 O 2 was reversed by iron sequestration or perR repressor gene deletion ( 238 ). Another study showed that the msaABCR operon of S. aureus regulates expression of genes involved in oxidative stress ( 239 ). Staphyloxanthin, a carotenoid pigment, is a strong antioxidant which is regulated by cold shock protein (CspA), alongside the organic hydroperoxide resistance gene which defends specifically against oxidative stress caused by organic hydroperoxides.…”
Section: Mechanisms Used By Macrophages To Kill S Aureus mentioning
confidence: 99%
“…Staphyloxanthin, a carotenoid pigment, is a strong antioxidant which is regulated by cold shock protein (CspA), alongside the organic hydroperoxide resistance gene which defends specifically against oxidative stress caused by organic hydroperoxides. This implies involvement of ROS resistance genes in persistence of S. aureus ( 239 ).…”
Section: Mechanisms Used By Macrophages To Kill S Aureus mentioning
confidence: 99%
“…The msaABCR operon is a four-gene operon that regulates several virulence factors (proteases as well as factors involved in pigmentation, toxin production, and capsule production), biofilm formation, persister cell formation, oxidative stress response, and antibiotic susceptibility in S. aureus [ 31 37 ]. We also showed that msaABCR deletion mutants are not defective in growth [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, S. aureus encodes two homologs of the thiol-dependent peroxidase Ohr, which are involved in detoxification of organic hydroperoxides, originating from lipid peroxidation (Dubbs and Mongkolsuk 2007;Mongkolsuk and Helmann 2002). The Ohr paralogs are redoxcontrolled by the thiol-based MarR/OhrR-family repressors MgrA and SarZ as well as by MsaB in S. aureus (Chen et al 2011;Pandey et al 2019). However, many other peroxiredoxins respond to oxidative stress, such as Tpx, Bcp or GpxA1 and GpxA2, which remain to be, characterized in future studies.…”
Section: Enzymatic Detoxification Systemsmentioning
confidence: 99%